FinTech Adoption and Financial Inclusion in Rural India - Jhamb, Anchit (Journal of Neonatal Surgery, 2025)
FinTech innovation has emerged as a transformative force in India’s evolving financial landscape, offering new pathways to bridge the long-standing divide between formal financial services and rural populations. As traditional banking institutions continue to grapple with challenges in reaching remote and underbanked areas, FinTech platforms—powered by mobile technology, digital identity frameworks, and real-time payments infrastructure—present scalable, cost-effective, and accessible alternatives. This paper explores the intricate relationship between FinTech adoption and financial inclusion in rural India, using a conceptual framework based on three core dimensions: Access, Usage, and Quality. Drawing from credible secondary sources such as the Reserve Bank of India (RBI), National Payments Corporation of India (NPCI), Telecom Regulatory Authority of India (TRAI), and Census data, the study conducts a comparative, state-wise analysis to examine how regional variations in digital infrastructure, gender equity, and policy orientation influence the effectiveness of FinTech services. It finds that while southern and western states demonstrate strong digital adoption and ecosystem readiness, others—particularly in central and eastern India—struggle due to infrastructural deficits, digital illiteracy, and trust-related concerns. The study also highlights the non-linear nature of FinTech impact, revealing that positive outcomes typically emerge only after certain threshold levels of smartphone penetration, internet access, and literacy are reached. In addition, it identifies gender disparity, cyber fraud concerns, and lack of vernacular design as significant obstacles to meaningful engagement with digital financial services. Based on these insights, the paper recommends targeted policy interventions in infrastructure expansion, digital education, localized FinTech design, and rural ecosystem development. Ultimately, this research underscores the importance of context-sensitive, inclusive, and collaborative approaches to digital finance, aiming to convert technological promise into sustainable financial empowerment for India’s rural population.